338 APPLYING STOPP/START CRITERIA TO A COHORT OF FALL PATIENTS IN THE COMMUNITY. (25th October 2022) - Feeney, L; Drumm, B; O'Malley, G; O'Sullivan, F; Hickey, P; Conlon, C
Abstract: Background: Integrated Care Teams for Older Persons (ICTOP) aim to transform care away from hospitals towards multidisciplinary community team care. Seventy percent of injuries requiring acute admission are caused by falls, costing €59 million annually, in addition to the overall morbidity and mortality burden. The Screening Tool of Older Person's Prescriptions / Screening Tool to Alert Doctors to Right Treatment (STOPP/START) identifies inappropriate prescribing and prescribing omissions, which should reduce falls risk and optimise patient outcomes. Methods: This prospective study randomly included 20 active ICTOP patients all of whom had fallen in the last 6 months. The STOPP/START Criteria were used to screen patient's prescriptions at time of referral. Results: The average age was 83 years old, 60% were male. Overall 45% had 1 fall, 15% had 2 falls, 20% had 3 falls and 20% had more than 5 falls. The most common comorbidities were hypertension (55%), heart disease (45%), and cognitive decline (40%). Regarding polypharmacy, 95% were prescribed more than 5 drugs, 55% were prescribed more than 10 drugs. Overall, 30% had a diagnosis of osteoporosis, 40% were on a bisphosphonate, while 65% were taking vitamin D and Calcium supplements. Of the 35% (7 patients) who had a previous fragility fracture, 1 had a DEXA scan and a further 3 were on the waiting list. Four of these patients were taking bisphosphonates and 6 were taking vitamin D and Calcium. Regarding STOPP criteria, 30% were taking opioids, 45% Proton Pump Inhibitors, 30% Calcium Channel Blockers, 30% Beta-blockers and 15% were taking Alpha-blockers. Conclusion: The study identifies a need for community teams to consider medications that increase falls risk and medications that should be initiated to optimise bone health. Community teams should have access to professional medical and pharmacy support, in addition to timely access to DEXA scans.